Privacy Preserving Data Mining: Implications and Advancements - Mohana Chelvan P, Dr. Perumal K (International Journal of Advanced Science and Technology, 2020)
Data mining drives business organizations across the world. Every organization uses data mining for getting tactics from the mammoth volume of archived operational data. At the same time, safeguarding the personal sensitive data and also mined personal sensitive knowledge is essential. Better data utility along with robust privacy preservation is the aim of privacy preserving data mining (PPDM). The data collected through organizations can be by them for the purpose not intended for and also sold to other organizations or persons. This paper analyses the issue by explaining various PPDM efforts. Keywords: privacy preservation, data mining, data publishing, differential privacy, feature selection stability.